Promoting Better Health for Young People Through Physical Activity and Sports (2001)
The USA's young people are, in large measure, inactive, unfit, and increasingly overweight. Physical inactivity threatens to reverse the decades-long progress in reducing deaths from cardiovascular diseases. Ultimately this could have a devastating impact on our national health care budget. This report from the Secretary of Health and Human Services and the Secretary of Education, and recently released by the White House, outlines ten strategies to promote health and reduce obesity through lifelong participation in enjoyable and safe physical activity and sports. Included is a bibliography and appendices of helpful materials. Full-text dowload possible.